Mafeje: scholar–activist with noble convictions. Issue 165 (2nd July 2020) - Jacobs, Peter T.
ABSTRACT: This critical review of an edited volume of Archie Mafeje's writings closes gaps in what is known about his political upbringing, his scientific methodology and posthumous intellectual influence. Trained in the radical political tradition of the Unity Movement of South Africa, Mafeje was a celebrated social theorist, broke with liberal functionalism in social anthropology and wrote prolifically. This important volume is silent on standout questions, such as: why did Mafeje, the mature scholar–activist, dissociate himself from practical politics after relocating from Cairo to Pretoria, given the crisis of the radical left in South Africa? To what extent did Mafeje wield his mastery of dialectical logic not only to interpret the world but actively change it? What was Mafeje's orientation toward agrarian transitions beyond capitalism in countries like South Africa? In response to these thematic questions, this essay synthesises insights from relevant chapters.